A Controlled Comparative Clinical Study On Vyoshadi Choorna With Takra And Dhatri Loha In The Management Of Pandu With Special Reference To Iron Deficiency Anaemia - Sanjana , S G; Bhat, Rupa (International Research Journal of Ayurveda & Yoga, 2020)
Pandu is explained as Rasapradoshaja Vikara and Raktavaha srhotodushti Vikara. It is Pitta predominant disorder involved with vitiation of all three Doshas and Rasa,Rakta ,Mamsa and Twak Dushyas. It has similar signs and symptoms that of iron deficiency anaemia like Panduta (pallar) Hridayaspandana (palpitation), Rukshatwacha (dried skin). It is very common prevalent disease in the society. Dhatri loha is explained in the context of Shoolapratishedha and is also indicated in Pandu. Dhatriloha is proved to be an effective formulation in the management of Pandu.Vyoshadi choorna explained in the context of Choornaprakarana in Sahasrayogam, mainly indicated in Pandu Roga. Trikatu, Ayasa choorna which have Teekshna ,Ushnagunas are predominant drugs can be effectively acts on Pandu Roga. Objective of the study is to know the efficacy of Vyoshadichoorna and Dhatriloha in Pandu.40 Patients of Pandu (IDA) will be taken one who fulfilling the inclusion criteria and divided into two groups randomly. GROUP A ; 20 patients of Pandu (IDA) is given Vyoshadichoorna GROUP B ; 20 patients of Pandu (IDA) is given Dhatriloha for 45 days. Both the groups are having similar effect on reducing the symptoms statistically. Among the subjective and objective parameters B group showed better result than Group A.